Heine, Carl & O'Connor, Dennis (2014) Teaching information fluencyRowman & Littlefield (Lanham MD & Plymouth UK) isbn978‐0‐8108‐9062‐6 215 pp £34.95 https://rowman.com/ISBN/9780810890626. (May 2015) - Johnson, Mike
Summary "Teaching" is in the title and the target audience is American, yet anyone using the internet can benefit from thumbing through these pages. Doing that will give you personal insight and strategies that will enhance any search, and raise awareness of the ethical dimension of dealing with what you find. Teachers of all subjects will enjoy the book's practical suggestions for embedding aspects of information fluency in class. If you feel the content of this book is relevant to you, I strongly suggest you borrow a copy for a while. Mike Johnson